Morphological and genetic variation in seven species of the endangered Chirostoma "humboldtianum species group" (Atheriniformes: Atherinopsidae) - Barriga Sosa, I.de los A.
(Es, En)
ilus., 41 ref.
Keywords: PECES; ANATOMIA ANIMAL; VARIACION GENETICA; COSTA RICA; CHIROSTOMA